Lecturers’ perspectives on enhancing student proficiency through academic integrity in logic and writing strategies - Abdel Rahman Mitib Altakhaineh; Marwan Jarrah; Afakh Younes (Studies in English Language and Education)
Developing critical thinking and effective communication skills through argumentative essays is crucial to the success of university students. This study aims to identify the most engaging strategies used in teaching writing argumentative essays for university students. In spite of this, identifying the most engaging strategies to teach this skill remains a challenge. To this end, three focus group discussions were conducted with 30 English-language lecturers and professors in Amman, Jordan. Additionally, an online survey was distributed among 30 English-language lecturers and professors in Amman, Jordan, and 50 students to rank the identified strategies. Semi-structured interviews were also conducted with English language professors and students. The rankings’ mean scores and frequency counts were calculated for each strategy. The findings of this study indicate similarities and differences between the two groups’ preferences for prewriting and post-writing strategies. Both groups agreed on the importance of prewriting and post-writing strategies in writing instruction. Nevertheless, lecturers favored brainstorming and outlining as a prewriting strategy and teacher feedback as a post-writing strategy. At the same time, students preferred the read-write model as a prewriting strategy and peer review as a post-writing strategy. These findings have significant implications for both educators and students. Using the read-write model and peer review as part of the curriculum can enhance engagement and learning outcomes by incorporating students’ preferences into teaching methods. Exposure to various strategies helps students identify the most effective approaches for themselves, fostering adaptability and proficiency in writing argumentative essays.